Patterns of recurrence of obstructing colon cancers after surgery for cure: a population‐based study. (18th September 2013) - Cortet, M.; Grimault, A.; Cheynel, N.; Lepage, C.; Bouvier, A. M.; Faivre, J.
Abstract Aim Little is known about patterns of recurrence in obstructing colon cancer (OCC) at a population level. The aim of this study was to determine the risk of recurrence following potentially curative surgery in OCC compared with that in uncomplicated colon cancer (CC). Method Data were obtained from the population‐based digestive cancer registry of Burgundy (France). Local and distant failure rates were calculated using actuarial methods. A multivariate analysis was performed using a Cox model. Results Obstructing colon cancer represented 8.5% of all colon cancers resected with curative intent (n = 3375). The 5‐year cumulative local recurrence rate was 14.2% for OCC and 7.6% for nonobstructing CC (P = 0.003). In the multivariate analysis, obstruction was an independent risk factor for local recurrence [hazard ratio 1.53 (1.01–2.34), P = 0.047]. The risk of local recurrence increased with advanced stage and age at diagnosis. The 5‐year cumulative rate for distant metastases was also higher in OCC than in nonobstructing CC (36.1 vs 23.1%; P < 0.001). The relative risk of distant metastasis was borderline significant in the multivariate analysis [hazard ratio 1.25 (0.99–1.59), P = 0.057]. Stage at diagnosis, macroscopic type of growth, period of diagnosis and sex were also significant prognostic factors. Age and subsite were not significant in the multivariate analysis. Conclusion It is possible to conduct special surveys in population‐based registries to determine the recurrence rate of CC. Recurrence remains a substantial problem and is more frequent in OCC than in nonobstructing CC. Efforts must be made to diagnose CC earlier. Mass screening is a promising approach.